2009
DOI: 10.1016/s0027-9684(15)31132-9
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported HIV Antibody Testing Among Latino Urban Day Laborers

Abstract: Objective To identify the characteristics of male Latino urban day laborers who self-report having tested for HIV. Methods A cross-sectional survey was conducted with 356 Latino day laborers, aged 18 to 40 years, who had been sexually active in the previous 12 months, from six day labor sites in the City of Los Angeles. Results Most of the men were single, mainly from Mexico and Guatemala, and had been employed as a day laborer less than 3 years; 38% had an annual income of $4,000 or less. Ninety-two perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 22 publications
2
13
0
Order By: Relevance
“…In addition, among individuals in the HIV-bundled protocol, those with an income greater than $10,000 were more likely to take an HIV test compared to those with a lower income. This is consistent with other research among day laborers which has found HIV testing to be more likely among those with a higher income (Solorio & Galvan, 2009). Day laborers with a higher income may have more access to promotional campaigns that stress the importance of HIV testing as well as locations to get tested for HIV.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In addition, among individuals in the HIV-bundled protocol, those with an income greater than $10,000 were more likely to take an HIV test compared to those with a lower income. This is consistent with other research among day laborers which has found HIV testing to be more likely among those with a higher income (Solorio & Galvan, 2009). Day laborers with a higher income may have more access to promotional campaigns that stress the importance of HIV testing as well as locations to get tested for HIV.…”
Section: Discussionsupporting
confidence: 91%
“…In the previously mentioned study of 356 sexually active Latino day laborers in Los Angeles, California, among the 46% (n=164) who reported having received an HIV test in the previous 12 months, one person reported being positive (Solorio & Galvan, 2009). However, that sample drew participants from six day labor sites where it was known that solicitation of Latino male day laborers for sex by other men occurred.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increasing research has examined HIV testing among Latinos. [13][14][15][16][17][18] Two novel intervention strategies (door-to-door outreach and trained peer educators) have demonstrated efficacy to increase HIV testing among heterosexual Latinos in North Carolina. 19,20 To date, however, few interventions have been developed to increase HIV testing among sexual and gender minority Latinos, 21,22 despite their recognition as a priority population for HIV prevention efforts.…”
mentioning
confidence: 99%